Isaac Briggs papers - Briggs, Isaac, 1763-1825.
Correspondence, writings, circulars, patents, and patent applications. Subjects include the Society of Friends, Elias Hicks and the Hicksites, appointments to office, abolition, slavery, and public education. Correspondents include William C.C. Claiborne, DeWitt Clinton, Albert Gallatin, Thomas Jefferson, John Mason, and members of the Briggs family.
Microfilm edition available in part
Microfilm produced from originals in the Manuscript Division.
In part, transcripts.
Surveyor, engineer, mathematician, and astronomer.
Collection material in English.
Keywords: Claiborne, William C. C. -- 1775-1817 -- Correspondence; Clinton, DeWitt, -- 1769-1828 -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Hicks, Elias, -- 1748-1830.; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Mason, John, -- 1766-1849 -- Correspondence; Briggs family -- Correspondence; Abolitionists; Hicksites; Patents; Public schools; Slavery -- United States; Society of Friends; Astronomers; Engineers; Mathematicians; Surveyors